Prevalência, distribuição espacial de focos e possíveis fatores de risco associados à Anemia Infecciosa Equina (AIE) no estado de Mato Grosso - Barros, Marcelo Luís (2017)
The present study estimated the prevalence of equine infectious anemia (EIA) in the Mato Grosso state, composed of three biomes (Amazonia, Cerrado and Pantanal). Serum samples of 3858 equids from 1067 herds (ranches), were collected between September and December 2014, in all 141 municipalities of the State. The agar gel immunodiffusion (AGID) was used to determine antibodies against EIA virus and the presence of one seropositive animal classified the herd as positive (focus). The estimated prevalence was 17.2% [95%CI: 14.9-19.8%] for herds and 6.6% [95%CI: 5.8-7.5%] for animals. The highest prevalence for herds and animals was found in the Pantanal biome with 36.1% [95% CI: 30.8-41.7%] and 17.0% [95% CI: 14.7-19.6%] respectively. The relative risk measure of spatial distribution was calculated according to the Kernel density where can be verified 3 major clusters with the highest prevalence values occurring in the Northwest (Amazon biome), Northeast (Cerrado biome) and south (Pantanal biome) regions. The high level of spatial relation was found among ranches with elevate intra-herd prevalence ranches localized in the Amazon and Cerrado biomes, while highest spatial relation with the focus was observed in the Pantanal biome. Variables related to management of farms reflecting human influence were associated to the presence of positive equids. Based on the results, it can be concluded that EIA are present in all evaluated biomes of the state and risk factor were associated to the human interference in the transmission process. In faced of this situation, the EIA control program need to be reevaluated and more prophylactic measures should be imposed for the disease control in the state of Mato Grosso.